Clinical criteria for proper diagnosis and treatment of perioperative anaphylaxis (Research, Society and Development, 2021)
Perioperative anaphylaxis is an unpredictable, severe and systemic hypersensitivity reaction mediated by IgE or non-mediated immunoglobulins, difficult to diagnose and potentially fatal. Furthermore, it is important to mention that perioperative IgE-mediated anaphylaxis is directly related to agents administered intravenously, occurring after anesthesia, with neuromuscular blocking agents (NMBs) and antibiotics being the main causal agents. After administration of the allergen, the evolution of the patient can range from only side effects, similar to those of medications in use, to serious evolutions such as cardiorespiratory arrests, showing a need to spread the theoretical and technical domain of the management of these situations to obtain better results. predictions. The mainstay of treatment for perioperative anaphylaxis includes: maintaining the airway patent, providing 100% oxygen, administering intramuscular (IM) or intravenous (IV) epinephrine, and volume replacement. Thus, since the patient can die in minutes, due to the acute situation intensifying quickly, urgent treatment is necessary. And for that, the present work brings the elucidation of diagnostic criteria (clinical picture, evolution and associated exams). In addition, it clarifies the management for the treatment of patients in perioperative anaphylaxis. For this bibliographical research, the databases of PubMed, Latin American and Caribbean Literature in Health Sciences (LILACS) and MEDLINE were used as reference.